2014
DOI: 10.1016/j.jmb.2014.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Specific Function of the Conserved Threonine Triad Responsible for Human l-Asparaginase Autocleavage and Substrate Hydrolysis

Abstract: Our long-term goal is the design of a human L-asparaginase (hASNase3) variant, suitable for use in cancer therapy without the immunogenicity problems associated with the currently used bacterial enzymes. Asparaginases catalyze the hydrolysis of the amino acid asparagine to aspartate and ammonia. The key property allowing for the depletion of blood asparagine by bacterial asparaginases is their low micromolar KM value. In contrast, human enzymes have a millimolar KM for asparagine. Towards the goal of engineeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
56
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 34 publications
4
56
0
1
Order By: Relevance
“…Similarly, a previous study of hASRGL1 showed that T219 and T186 provide an essential hydrogen bond network that facilitates both intra-molecular processing and substrate catalysis where it was reported that T219V, T219A, and T186V variants required large amounts of glycine to achieve (partial) cleavage but displayed no detectable L-Asn hydrolysis. 3 We initiated a mutagenesis study by constructing N62D/A, T186A/S, and T219A/S active site variants to assess their role in substrate catalysis as well as processing. Using the cp-hASRGL1 platform as a way to obtain fully activated enzyme along with the use of the asparaginase substrate analogue, L-aspartic acid β -hydroxamate (AHA) provided an ideal way to detect activity of these mutated variants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, a previous study of hASRGL1 showed that T219 and T186 provide an essential hydrogen bond network that facilitates both intra-molecular processing and substrate catalysis where it was reported that T219V, T219A, and T186V variants required large amounts of glycine to achieve (partial) cleavage but displayed no detectable L-Asn hydrolysis. 3 We initiated a mutagenesis study by constructing N62D/A, T186A/S, and T219A/S active site variants to assess their role in substrate catalysis as well as processing. Using the cp-hASRGL1 platform as a way to obtain fully activated enzyme along with the use of the asparaginase substrate analogue, L-aspartic acid β -hydroxamate (AHA) provided an ideal way to detect activity of these mutated variants.…”
Section: Resultsmentioning
confidence: 99%
“…2 Furthermore, the hASRGL1 asparaginase activity has generated interest in the therapeutic development of hASRGL1 as a potentially nonimmunogenic alternative to the bacterial asparaginases used to clinically treat acute lymphoblastic leukemia. 3 …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…ASNases are classified into two families: i.e., bacterial type or type I and type II, and plant-type or type III enzymes. The bacterial type II enzymes have been used in treating ALL because of their low micromolar K m value and relatively easier preparation, whereas the human enzyme, a type III enzyme, has a millimolar K m value for ASNase [ 25 ]. The human enzyme is poorly suitable for cancer treatment because of reduced activities.…”
Section: Targeting Specific Amino Acid Starvation In Cancer Therapmentioning
confidence: 99%